Caveolin‐1 associated with severe (pediatric‐onset) presentation of pulmonary arterial hypertension. (18th July 2022) - Farrell, Rachel; Colglazier, Elizabeth; Parker, Claire; Stevens, Leah; Austin, Eric D.; Fineman, Jeffrey R.
Abstract: There has been a growing interest in the role that genetic factors influence pediatric pulmonary vascular disease. In fact, data suggests that genetic factors contribute to 42% of pediatric‐onset pulmonary hypertension. Although animal and human studies suggest that aberrations in Caveolin1 ( CAV 1) signaling participate in the development of pulmonary vascular disorders, limited reports of CAV1 ‐associated heritable pulmonary arterial hypertension (HPAH) exist. This is a case report of a 2‐year‐old female with late recognition of HPAH due to a CAV1 pathogenic variant: c.474del, (p.Leu159Serfs*22)(NM_001753.5). The pedigree demonstrates autosomal dominant transmission with reduced penetrance of PAH, suggestive that additional genetic or environmental factors modify PAH development. Genetic testing and the discovery of rare genetic alterations in PAH during infancy and childhood may aid in identifying disease etiologies, guide therapeutic decisions, and ultimately identify novel therapeutic targets. Moreover, CAV1 genetics implicate variable expressivity and incomplete penetrance for HPAH and underscores the utility of predictive genetic testing for unaffected family members no matter their age.